Fractal Geometry Tools in Studying the Formal Characteristics in the Urban Structure of the Traditional Al-Mutanabbi Street in Baghdad (Journal of Engineering, 2025)
The research focuses on examining the level of harmony in the formal characteristics among the elements of the traditional Baghdad alley, from individual components to the entire area. Numerous studies have highlighted the unity and cohesion in the urban structures of traditional Arab urban environments, including Baghdad alleys, despite the diversity of the urban landscape. The study's theoretical aspect focuses on the visual features of the traditional urban environment, emphasizing the concept of diversity within unity. This is explored through specialized studies in the field. The applied part of the study involves using fractal geometry tools, specifically the box-counting method, to measure the degree of harmony and variation within different parts of the urban environment. This assessment starts from individual parts and expands to the panorama on both sides of the alley. This research aims to highlight the visual characteristics of traditional alleys that are essential to their urban framework. It is imperative to incorporate these characteristics into new urban plans to effectively uphold the local identity. The research problem is the lack of studies on fractal geometry as an analytical tool for designers to achieve specific formal characteristics, such as harmony between parts and the whole, particularly in the context of traditional paths. The research took into account the historical, social, and cultural influences on urban design in Al-Mutanabbi Street. The findings revealed that these influences significantly shape the urban framework and enhance the cohesion among different elements.